Chinese soy-based microbiome and associated microbial risks: a metagenomic investigation - Xuesong Xiang; Yingying Li; Junbin Ye; Baolong Li; Guozhong He; Mingyu Zhu; Jiawen Zhang; Bike Zhang; Ming Miao; Yuexin Yang (npj Biofilms and Microbiomes)
Abstract Fermented foods are a longstanding part of the Chinese diet and have been recognized for promoting gut microbial diversity. However, their microbial composition remains poorly defined, raising concerns about potential exposure to pathogens and antibiotic resistance genes (ARGs). Using shotgun metagenomics, we examined microbiota of 93 representative samples spanning three major categories of traditional Chinese fermented soybean products. We identified distinct microbial and functional profiles across food types, with antagonism between beneficial taxa (Bacillales and Lactobacillales) and harmful Enterobacterales. Comparative analysis with public Chinese gut microbiomes revealed species- and strain-sharing between fermented foods and human gut microbiota, identifying certain products as sources of clinically relevant pathogens, including Klebsiella pneumoniae and Klebsiella quasipneumoniae. Horizontal gene transfer analysis highlighted potential transfer of ARGs (e.g., efflux pump genes) from food microbes to gut microbiota. Our findings underscore the need to integrate microbial surveillance into traditional fermentation to balance health benefits with food safety.